PENINGKATAN PERTUMBUHAN DAN HASIL KEDELAI YANG DITANAM DALAM KONDISI JENUH AIR MELALUI PEMBERIAN P ANORGANIK DAN KOMPOS JANJANG KOSONG SAWIT DI ULTISOL - Annisa Wulandari; Hesti Pujiwati; Bambang Gonggo Murcitro; Marwanto; Elsa Lolita Putri (BPFP Universitas Bengkulu, 2023)
[ENHANCING GROWTH AND YIELD OF SOYBEAN GROWN UNDER WATER-SATURATED CONDITIONS BY INORGANIC P AND EMPTY FRUIT BUNCH COMPOST AMENDMENTS IN ULTISOL]. The saturated soil culture practices with which to obtain high yield of soybean in Ultisol, characterized by high acidity, nutrient deficiencies and imbalances, should be developed. This study was conducted to evaluate the beneficial effects of empty fruit bunch (EFB) compost combined with inorganic P application on growth and yield of soybean under water-saturated culture in Ultisol. This research was carried out from September to December 2022 in the rice field located in Kemumu Village, Arma Jaya District, North Bengkulu Regency, Bengkulu Province at an altitude of ±541 m above sea level. The field experiment was performed in factorial scheme based on a randomized complete block design with three replications. The experimental treatments included EFB compost as first factor at four levels (0, 5, 10, and 15 t/ha) and application of SP36 as second factor at four rates (0, 75, 150, and 225 kg/ha). Results show that Ultisol amended with a combination of 15 t/ha EFB compost and 75 kg/ha P2O5 resulted in the highest number of seeds per plant (about 142.266 seeds). The number of productive branches, fresh shoot weight, root dry weight, and root nodule weight was the highest in soil solely ammended with EFB compost at 15 t/ha. The sole P application at 225 kg/ha significantly (p<0.05) increased root dry weight and root nodule weight. Thus, under saturated soil culture, application of EFB compost and inorganic P in sole or combination would be the recommended nutrient management practice for enhancing soybean agronomic prformances in this acid soil.